1997
DOI: 10.1021/jp972678f
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Discotic Liquid Crystalline Compounds at the Air−Water Interface

Abstract: We have used grazing incidence X-ray diffraction and X-ray specular reflectivity to study the behavior of platelike hexaalkoxytriphenylene derivatives at the air−water interface. The data are consistent with a two-dimensional columnar mesophase, wherein the molecules are arranged “edge-on” to the water surface, with intercolumnar spacings of 13−19 Å. We propose a molecular conformation in which hydrophobic tails lie parallel to the water surface so as to allow the hydrophilic oxygen atoms to directly contact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…At the water interface exist liquid crystals that orient horizontally (flat‐on) and that orient vertically (edge‐on). Regarding the phenomenon, many authors have reported on the study of orientation behavior of the discotic liquid crystal at the air‐water interfaces 32–41. According to them, the benzene condensed ring–based triphenylene ring and truxene ring with long‐chain alkyls orient edge‐on (vertical to the interface) and the heterocyclic ring–based phthalocyanine, triaryl melamine, and azacrown rings orient flat‐on (horizontal to the interface).…”
Section: Horizontal Orientation Of Discotic Liquid Crystal31mentioning
confidence: 99%
“…At the water interface exist liquid crystals that orient horizontally (flat‐on) and that orient vertically (edge‐on). Regarding the phenomenon, many authors have reported on the study of orientation behavior of the discotic liquid crystal at the air‐water interfaces 32–41. According to them, the benzene condensed ring–based triphenylene ring and truxene ring with long‐chain alkyls orient edge‐on (vertical to the interface) and the heterocyclic ring–based phthalocyanine, triaryl melamine, and azacrown rings orient flat‐on (horizontal to the interface).…”
Section: Horizontal Orientation Of Discotic Liquid Crystal31mentioning
confidence: 99%
“…[14,17,18] XRR and GIXRD studies of 3a and 3b at the air±water interface unambiguously established monolayer edge-on columnar structure, albeit with a 10±30 % occupied second layer. [19] Furthermore, a detailed analysis of the XRR profiles (Fig. 2c), together with simple computer modeling, answered a long-standing question about the conformation of the alkoxy tails at the air±water interface.…”
mentioning
confidence: 96%
“…[21] GIXRD provided information on the structural order at a molecular level, while the BAM measurements in the configuration employed imaged inhomogeneities in the birefringence. For all triphenylene derivatives studied, only a single GIXRD peak was observed, [19,21] corresponding to an intercolumnar d-spacing of~14 . Neither the 001 peak, corresponding to the intracolumnar correlations, nor hkl peaks, corresponding to crystalline intercolumnar positional correlations, were obResearch News Fig.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Adoption of an edge-on orientation is generally inferred from the Π-A isotherm yielding molecular areas smaller than that possible for a face-on orientation. X-ray reflectivity and grazing incidence X-ray diffraction data confirmed the edge-on orientation was favored on compression even for triphenylenes symmetrically substituted with six identical alkoxy groups [9]. Disc-shaped molecules with a variety of other structures have also been studied as monolayers and thin films [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 89%